A Study of Agricultural Development of the Environment: - (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Agriculture and the environment are closely linked it significantly affects the usage of land,soil, water, biodiversity, and the landscape. The biological equilibrium has been disrupted by intensiveagriculture, which has also significantly altered cropping patterns, how agricultural inputs areemployed, and how soil fertility is managed. Land cropping intensity, irrigated area, and rice-wheatHYVs has all increased considerably. The area devoted to inland natural fisheries, feed, and pulses, onthe other hand, is steadily shrinking. Crop rotation, intercropping, and other traditional croppingtechniques are slowly dying out. And the study in which discussed about Agriculture An Overview ofCommencement, Agriculture, Environmental Impact of Agriculture, Agriculture in degradation,Agricultural pollution, Agriculture and Ecology, Concept of Sustainable Development and Issues ofAgro Sustainability.